Analysis of Employee Training Plan PT. Batam Aero Technic Based on the Calendar of Training for One Year - Mareta Naoksavia Biva; Kifni Yudianto (CV. Rayyan Dwi Bharata, 2023)
Planning or Planning is a way to decide what steps must be taken to achieve a goal within a certain period of time. While training is learning that is prepared so that the quality and quality of an individual can increase in carrying out their duties and responsibilities. Training at PT. Batam Aero Technic is more focused on the ability to improve the performance of its employees according to their jobs. This study aims to determine the management of employee training planning in PT. Batam Aero Technic especially in the implementation and scheduling process based on the Calendar of Training in one year. This research is classified as participatory research or direct research, using interview techniques, observation, and documentation. Data analysis in this study used a qualitative descriptive method. The research was conducted in the Quality Assurance Training department using primary and secondary data collection. Primary data includes the results of interviews with respondents, while secondary data was obtained from company documents, namely manuals and journals related to Manual Procedure Training at PT. Batam Aero Technic. Based on the results of the research that has been done, it can be concluded that the main objective of training at PT. Batam Aero Technic has been running quite well as evidenced by the increased knowledge and ability of employees. The training material provided is quite appropriate by providing material in stages and in accordance with the functional jobdesk of each employee. Furthermore, the method used in determining employee training is considered to be in accordance with the company's operational standards so that employees can attend training properly. The scheduling process in training planning uses planning based on the Calendar of Training in one year which is very well prepared, this certainly makes the planning process for PT. Batam Aero Technic becomes more effective. because employees can find out what training will be carried out each month